PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS (Studi pada Perusahaan dalam Sektor Barang Konsumen Primer yang Terdaftar di Bursa Efek Indonesia Periode 2016-2019) - Dwi Nur Faida; Paulus Th. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2022)
Working capital management is important for the company, because working capital management includes managing the company's operational activities. Efficient working capital management can increase the company’s profitability. Meanwhile, bad working capital management can cause decreased profitability and even losses, as experienced by several companies in the consumer non-cyclicals sector. The companies that experience this loss are increasing from year to year. Even though it is also known that companies listed on the Indonesia Stock Exchange in this sector are increasing every year. Therefore, this study was conducted to know and find evidence about the effect of working capital management which includes the average collection period, inventory conversion period, payable deferral period, and operating cash flow on the profitability of consumer non-cyclicals sector companies listed in the Indonesia Stock Exchange from 2016 – 2019 period. The sample selection method used is the purposive sampling method which is obtained from 79 companies with a total sample of 276. The data analysis technique used multiple regression analysis with SmartPLS 3.2.9 version. The results showed that the inventory conversion period had a negative and significant effect on profitability. Then, operating cash flow had a positive and significant effect on profitability. Meanwhile, the average collection period and the payable deferral period have no effect on the company's profitability.